2019
DOI: 10.2147/dddt.s212520
|View full text |Cite
|
Sign up to set email alerts
|

<p>Physicochemical properties and drug-release mechanisms of dual-release bilayer tablet containing mirabegron and fesoterodine fumarate</p>

Abstract: Introduction: In this study, a dual release bi-layer tablet containing Fesoterodine fumarate (Fst) 5 mg and Mirabegron (Mrb) 50 mg was prepared to investigate the different release behavior of each drug in bilayer tablet. The bilayer tablet was prepared based on monolayer-tablet formulation of each drug. Methods: The optimized bi-layer tablet showed an in vitro dissolution profile similar to commercial reference tablets Toviaz and Betmiga, based on a satisfactory similarity f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…For ATR-FTIR imaging, the analyzed samples must be placed on an internal reflectance element, and measurements are usually taken at the interface between the analyzed sample and the medium. This method has been used to investigate the influence of pH and/or ionic strength on drug release from a hydrophilic polymer matrix system [ 76 , 77 ], to study the drug release from multi-layer and/or multi-drug tablets [ 78 , 79 ], as well as thin films [ 80 ]. In addition, ATR-FTIR imaging was coupled with DEM to model the release of nicotinamide from HPMC matrix tablets [ 81 ].…”
Section: Drug Release Modelingmentioning
confidence: 99%
“…For ATR-FTIR imaging, the analyzed samples must be placed on an internal reflectance element, and measurements are usually taken at the interface between the analyzed sample and the medium. This method has been used to investigate the influence of pH and/or ionic strength on drug release from a hydrophilic polymer matrix system [ 76 , 77 ], to study the drug release from multi-layer and/or multi-drug tablets [ 78 , 79 ], as well as thin films [ 80 ]. In addition, ATR-FTIR imaging was coupled with DEM to model the release of nicotinamide from HPMC matrix tablets [ 81 ].…”
Section: Drug Release Modelingmentioning
confidence: 99%
“…It was found that only at relatively high flow rates did the dissolution profile resemble that of zero-order release formulations, attributed to the erosion of the gel layer [64]. In a more recent study by Lee et al, the dissolution behaviour of Fesoterodine fumarate (Fst) and Mirabegron (Mrb) was studied in a bilayer tablet where extended release was desired for both APIs [88]. Several techniques were implemented to characterize the dissolution behaviour of the two drugs in the bilayer tablet, including camera imaging, SEM, swelling and erosion studies, USP dissolution testing and ATR-FTIR spectroscopic imaging.…”
Section: Multi-layer and Multi-drug Tabletsmentioning
confidence: 99%
“…This resulted in a decreased dissolution profile as compared to the dissolution profile of the monolayer tablet. The use of ATR-FTIR spectroscopic imaging in this study revealed the amount of drug transfer from one layer to the other and vice versa in a dual-release bilayer-tablet system [ 88 ]. This paper demonstrates that, with more complex drug delivery systems under development, chemical imaging will become essential in the characterisation of the drug release mechanisms underlying dissolution profiles obtained via USP standard testing.…”
Section: Advances In Ftir Spectroscopic Imaging For Tablet Dissolutio...mentioning
confidence: 99%
“…They prepared and investigated the release behaviour of each drug in the bilayer tablet. 9 A previous study found that either the formulation was not targeted to the desired region, or if it was targeted, there was a deficiency in prolonging release. Hence, the present study aimed to develop a suitable delivery system that would allow Fesoterodine to be absorbed well through the intestinal region and prolong its release with the help of a pH dependant minitablet in the capsule system.…”
Section: Introductionmentioning
confidence: 99%